Resistência de união e microinfiltração em restaurações de resina - Lima, Luciana Monti; Motisuki, Cristiane; Lopes, Beatriz Maria Valério; Santos-Pinto, Lourdes Aparecida Martins dos [UNESP] (My University, 2011)
This in vitro study evaluated microtensile bond strength (MBS) and microleakage of composite resin restorations in cavities prepared with ultrasonic diamond tip and diamond bur coupled to high-speed handpiece. The MBS test used 6 third molars that after enamel occlusal removal were randomly divided in two groups according to the 2 cutting instruments that were applied on dentin surface during 60 seconds. Blocks of 3 mm composite resin were made over the dentin surface treated and after 24  hours each tooth produced sticks with a cross-sectional area of 0.81 mm2 that were submitted to a microtensile test for bond strength measure. To the microleakage test, standardized class V cavities with enamel and dentin margins were prepared on the facial and lingual surfaces of 12 third molars randomly divided in two groups according cutting instruments. After composite resin restoration, the teeth were subjected to thermocycle, immersed in 50% silver nitrate solution and sectioned to evaluate the percentage of microleakage under stereomicroscope. All data were analyzed by ANOVA and Tukey test (p ≤ 0.05). The results showed that the composite resin restorations made on dentin surface treated by ultrasonic diamond tip presented bond strength values significantly higher (p = 0.03). Microleakage in enamel and dentin margins was not different between groups. The ultrasonic diamond tip seems to be a promising alternative cutting instrument for restorative dental treatment.

Este estudo in  vitro avaliou a resistência de união por microtração (RUM) à dentina e a microinfiltração em restaurações de resina composta após preparos cavitários com ponta diamantada ultrassônica e ponta diamantada em alta rotação. Para o teste de RUM, utilizaram-se seis terceiros molares que, após remoção do esmalte oclusal, foram aleatoriamente distribuídos para tratamento da superfície da dentina exposta durante 60 segundos com os dois instrumentos de corte. Blocos de resina composta com 3 mm de altura foram confeccionados sobre a superfície tratada e, após 24 horas, cada dente forneceu espécimes com área de secção transversal de 0,81 mm2 , que foram submetidos à microtração para medida de sua resistência de união. Para o teste de microinfiltração, cavidades classe V padronizadas com margens em esmalte e dentina foram preparadas nas faces vestibulares e linguais de 12 terceiros molares distribuídos aleatoriamente entre os dois instrumentos de corte. Após a restauração com resina composta, os dentes foram submetidos à termociclagem, imersos em solução de 50% de nitrato de prata e seccionados para análise em lupa estereoscópica das porcentagens de microinfiltração. Todos os dados foram analisados pelo teste ANOVA e Tukey (p ≤ 0,05). Os resultados evidenciaram que a ponta diamantada ultrassônica promoveu valores de resistência de união significantemente maiores (p = 0,03). A microinfiltração nas margens em esmalte e dentina não foi diferente entre os grupos. A ponta diamantada ultrassônica parece ser um instrumento de corte alternativo promissor no tratamento dentário restaurador.
Bond strength and microleakage of composite resin restorations regarding the cutting instrument
Keywords: Ultrasonics; Diamond; Dental cavity preparation; Tensile strength; Dental leakage; Dentin; CVD (chemical vapor deposition); Ultra-som; Preparo de cavidade dentária; Microinfiltração